2018
DOI: 10.1071/bt17192
|View full text |Cite
|
Sign up to set email alerts
|

Conservation genetics and demographic analysis of the endangered cycad species Cycas megacarpa and the impacts of past habitat fragmentation

Abstract: The limited seed dispersal range of cycads, longevity of individuals, including a long juvenile phase, coupled with dioecy, suggest that the impacts of habitat fragmentation are not straightforward. Cycas megacarpa K.D. Hill. is an endangered cycad that occurs in a highly fragmented landscape derived from past agricultural land clearing. Current threats continue to be land clearing for both urban and rural developments and major infrastructure development for coal seam gas. This study investigated the effect f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 90 publications
2
11
0
Order By: Relevance
“…The Cycas species, with similar life history and reproductive characteristics, are thought to have a high level of genetic variation within populations and significant genetic differentiation among populations (Liu et al, 2015). The significant genetic differentiation and clear genetic structure observed in the C. taiwaniana complex may be explained by limited gene flow (Feng et al, 2014;James et al, 2018), which had also been reported for other Cycas species (Zhao and Gong, 2015;Feng et al, 2017). The effective propagation distance of Cycas species is 2-7 km (Yang and Meerow, 1996).…”
Section: Phylogeographical Patternmentioning
confidence: 86%
“…The Cycas species, with similar life history and reproductive characteristics, are thought to have a high level of genetic variation within populations and significant genetic differentiation among populations (Liu et al, 2015). The significant genetic differentiation and clear genetic structure observed in the C. taiwaniana complex may be explained by limited gene flow (Feng et al, 2014;James et al, 2018), which had also been reported for other Cycas species (Zhao and Gong, 2015;Feng et al, 2017). The effective propagation distance of Cycas species is 2-7 km (Yang and Meerow, 1996).…”
Section: Phylogeographical Patternmentioning
confidence: 86%
“…Genetic diversity is not often found to be correlated with the population size (James et al 2018), which is also consistent with our study. Population PZH seems to be the center of refugium for its considerable numbers of Nc.…”
Section: Implications For Conservationsupporting
confidence: 93%
“…Although the phylogeographical pattern of C. panzhihuaensis could not be clearly revealed because the great loss of population size in populations WQ, JPD, SL and GH, we evaluated the overall genetic diversity of C. panzhihuaensis within and among the current populations in different levels (cpDNA, nDNA and SSR), which can guide us in the conservation practices. Genetic diversity is not often found to be correlated with the population size (James et al 2018), which is also consistent with our study. Population PZH seems to be the center of refugium for its considerable numbers of Nc.…”
Section: Implications For Conservationsupporting
confidence: 93%